THE ISSUE OF CLARITY IN LEGAL LANGUAGE – LINGUISTIC AND THEORETICAL-LEGAL ASPECTS - ANDRUSZKIEWICZ, Marta (Comparative Legilinguistics, 2018)
The aim of this article is to present the notion of clarity as considered from the linguistic and theoretical-legal perspectives. Clarity, similarly to communicativeness and adequacy, constitutes a desirable feature of any legal text. The necessity of considering the three features has been formulated in normative regulations regarding the tenets of a legislative technique. Furthermore, the requirement is part of a constitutional principle of proper legislation. Clarity characterizes legal texts; it is required due to the editorial correctness which should be achieved in the process of the writing of a legal text. It arises from the rules for making laws according to the principles of state under the rule of law. The requirement for the consideration of the desirable features of a legal text by a legislator has both formal and ethical dimensions, because the clarity of a legal text not only constitutes a structural property but also guarantees that values such as legal certainty, legal security of citizens as well as trust in both state and law are recognised. The point is, however, that it is not always possible to achieve such clarity. The objective of this analysis is to investigate the causes which confirm that the requirement for the clarity of any legal text is complicated and not easy to meet. It is due to the fact that the requirement is conditioned not only by strictly legal factors but also linguistic, contextual as well as ethical ones.